FUNGSI UANG DALAM PANDANGAN ULAMA - Darsi Ahmadan (Program Studi Perbankan Syariah, 2021)
Money is the driver of the economy, with money economic activities, both production, distribution and consumption will run smoothly. Some people think that the money they currently have is a full right for them, so they use it arbitrarily, some even keep it unproductive. This study aims to explain how the function of money according to Islam and how the Messenger of Allah gave an example to use money. This type of research is library research and uses data collection techniques by collecting books, journals, and previous works related to money. The data collection technique that the researcher uses is documentation and uses qualitative data analysis techniques. All of the collected data were analyzed by means of deductive thinking. According to the results of the study, the function of money according to Islam is divided into public goods, where money is considered as the property of the community, it should not be privately owned (private goods), Islamic economics prohibits the owner of money from holding or hoarding. The money is in excess with an unnatural amount and is allowed to settle unproductively, but it must be used for economic activities, the money must be enjoyed by the whole community. While the flow concept is the concept of flowing, namely money must flow and rotate in economic activity, used in real sector investment and various contracts that have been exemplified by the Prophet Muhammad, such as: mudharabah, musharaka, wadiah and others.